Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
The Bank of Slovenia (BoS) officially pursues a policy aimed at lowering inflation to European levels and maintaining the stability of the currency. Since 1997, the intermediate target of the BoS has been the growth of the broad monetary aggregate M3 (defined as the daily average of the last quarter of the year relative to the same period last year). During 1995-98, to limit the impact of large inflows of foreign capital on the domestic economy and achieve its monetary targets, the BoS has resorted to heavy capital controls.